Faktor-Faktor yang Memengaruhi Implementasi Sistem Akuntansi Keuangan Desa di Kecamatan Wuluhan, Kecamatan Balung, Kecamatan Semboro, Kabupaten Jember - Dimas Khoirul Amin; Nurshadrina Kartika Sari; Nanda Widaninggar (JAKUMA : Jurnal Akuntansi dan Manajemen Keuangan, 2024)
This research aims to determine the partial and simultaneous influence of behavior, village financial management, clarity of goals, superior support, and training on the implementation of the village financial accounting system. The data used in this research are primary data and secondary data. The research results show that the variables of attitude, perception, learning, clarity of goals, support from superiors, training partially have a significant effect on the implementation of the village financial system. while motivation and emotions partially do not have a significant effect on the implementation of the village financial system. and simultaneously the variables of attitude, motivation, emotions, perception, learning, clarity of goals, support from superiors, and training have a significant effect on the implementation of the village financial system in Wuluhan District, Balung District, Semboro District, Jember Regency